Addressing problems for labour not problems of labour: the need for a paradigm shift in work and industrial relations policy. (2nd January 2023) - Wright, Chris F
ABSTRACT: This article argues that the policy framework governing work and industrial relations in Australia and other liberal market economies is stuck in an outdated paradigm fixated on solving problems of labour that have diminished or no longer exist, such as excessive union power and overt forms of industrial conflict. This policy framework is poorly equipped for addressing increasingly urgent problems for labour, such as growing inequality and workforce insecurity. Drawing upon neo-pluralist ideas and the findings emerging from industrial relations research, the article presents recommendations for what a new industrial relations policy framework would look like. It advocates for the adoption of a neo-pluralist policy paradigm focused on the creation of quality employment, worker wellbeing, redistribution in bargaining and wage determination, fairer labour immigration policies, stronger protections against gender-based inequalities, and increased job security.